Stem cell-based therapy for systemic lupus erythematous - Zare Moghaddam, Maryam; Mousavi, Mohammad Javad; Ghotloo, Somayeh (Journal of translational autoimmunity (Online), 2024)
Systemic lupus erythematosus (SLE), an autoimmune disease, is among the most prevalent rheumatic autoimmune disorders. It affects autologous connective tissues caused by the breakdown of self-tolerance mechanisms. During the last two decades, stem cell therapy has been increasingly considered as a therapeutic option in various diseases, including parkinson's disease, alzheimer, stroke, spinal cord injury, multiple sclerosis, inflammatory bowel disease, liver disease, diabete, heart disease, bone disease, renal disease, respiratory diseases, and hematological abnormalities such as anemia. This is due to the unique properties of stem cells that divide and differentiate to the specialized cells in the damaged tissues. Moreover, they impose immunomodulatory properties affecting the diseases caused by immunological abnormalities such as rheumatic autoimmune disorders. In the present manuscript, efficacy of stem cell therapy with two main types of stem cells, including mesenchymal stem cell (MSC), and hematopoietic stem cells (HSC) in animal models or human patients of SLE, has been reviewed. Taken together, MSC and HSC therapies improved the disease activity, and severity in kidney, lung, liver, and bone (improvement in the clinical manifestation). In addition, a change in the immunological parameters occurred (improvement in immunological parameters). The level of autoantibodies, including antinuclear antibody (ANA), and anti-double-stranded deoxyribonucleic acid antibodies (dsDNA Abs) reduced. A conversion of Th1/Th2 ratio (in favor of Th2), and Th17/Treg (in favor of Treg) was also detected. In spite of many advantages of MSC and HSC transplantations, including efficacy, safety, and increased survival rate of SLE patients, some complications, including recurrence of the disease, occurrence of infections, and secondary autoimmune diseases (SAD) were observed after transplantation that should be addressed in the next studies. •Both mesenchymal (MSC), and hematopoietic stem cells (HSC) can improve the disease activity, and severity in systemic lupus erythematous (SLE).•Treatment with MSC, and HSC results in an improvement in the skewed immunological parameters in favor of the disease improvement.•In spite of the clear efficacy of MSC and HSC transplantations, some complications occurs needing to be managed.